PERBEDAAN TEKNIK CAROUSEL DENGAN TEKNIK EACH ONE TEACH ONE DALAM PEMBELAJARAN MATEMATIKA - Elfa Rafulta; Adri Nofrianto (Universitas Islam Negeri (UIN) Mataram, 2017)
The Students’ mathematics learning outcomes of is still under the expected score. This condition is caused by the lack of students’ anthusiasm, students’ involvement in learning process. Research in applying Carousel Technique and Each One Teach One Technique have resulted a positive effect to students learning outcomes. These models motivate students to express their ideas, works independently and develop their creativity in solving the given problem. This research aims to compare the effectiveness of both technique. The randomized post test only comparison group design is used in the research. The population is all of students of grade 10th of SMAN 5 Pariaman in year 2015/2016. Two classes are chosen as samples. The annava t-test and SPSS software are used to test the hypothesis. Based on the data, is obtained. Since , it means that is rejected. It can be concluded there is significant differences between students’ learning outcome that is taught with applying Carousel Technique and students’ learning outcome Each One Teach One Technique.